Nanocrystalline silicon emitter optimization for Si‐HJ solar cells: Substrate selectivity and CO2 plasma treatment effect. Issue 2 (8th December 2016) - Mazzarella, Luana; Kirner, Simon; Gabriel, Onno; Schmidt, Sebastian S.; Korte, Lars; Stannowski, Bernd; Rech, Bernd; Schlatmann, Rutger
Abstract : We investigated hydrogenated nanocrystalline silicon (nc‐Si:H) films as doped emitter layers for silicon heterojunction solar cells. Firstly, we focused on the effect of the nc‐Si:H deposition conditions and film growth on the intrinsic hydrogenated amorphous silicon passivation layer ((i)a‐Si:H) underneath. Three different p‐doped emitters were compared: nc‐Si:H, nc‐SiO x :H, and a‐Si:H. We found that the nc‐Si:H and nc‐SiO x :H growth enhances the passivation of the epitaxy‐free (i)a‐Si:H layer, yielding implied open circuit voltages above 730 mV. Secondly, for (p)nc‐Si:H emitters, we observed a trade‐off between fill factor (FF) and open circuit voltage ( V oc ) by using two types of (i)a‐Si:H films. A slight epitaxy of the (i)layer seems to promote the rapid nucleation of nc‐Si:H, thereby positively affecting the FF (79.5%) and series resistance but reducing V oc (670 mV). Contrarily, on well‐passivating (i)a‐Si:H the nc‐Si:H nucleation is more difficult resulting in S‐shaped I – V curves, presumably due to low built‐in voltage and a poor emitter/TCO contact. To circumvent this dilemma, a CO2 plasma treatment is used to oxidize the a‐Si:H surface before the nc‐Si:H emitter deposition thereby enhancing nucleation. Accordingly, a FF of 74.5% with V oc of 727 mV is reached in the best device, yielding a conversion efficiency of 21%. HR‐TEM micrograph of the front layer stack of the solar cell. The image shows a region close to the valley between two pyramids. From bottom to top: c‐Si substrate, (i)a‐Si:H passivation layer showing epitaxially grown regions, (p)nc‐Si:H emitter layer, and In2 O3 :Sn (ITO). Yellow lines highlight layers and individual crystals. Silicon zone axis orientation is <101>.